Advance in research on microbial mechanism of refuse degradation in landfill - LONG Yan; SHEN Dong-sheng; LAO Hui-min; HU Hong (浙江大学学报. 农业与生命科学版, 2006)
Microbe acts as the leading actor in refuse degradation of landfill. Microbial procedure and microbial mechanism of refuse degradation, microbial groups involved, activity of microbes and factors affecting the activity are reviewed and development trend of future research in this area are discussed.